Analisa Komunikasi Internal dan Eksternal Dinas Syariat Islam Dalam Penerapan Syariat Islam di Kabupaten Aceh Tenggara - Roezaini Soefi (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
This study aims to analyze the communication and communication process carried out by the Islamic Sharia Service internally and externally in the application of Islamic Shari'a in Southeast Aceh and to determine the relationship between internal and external communication of the Islamic Sharia Service in the application of Islamic Sharia in Southeast Aceh Regency, the Subjects and Objects of this research. is the Islamic Sharia Service of Southeast Aceh Regency. This study uses a qualitative descriptive method with the observation method. The results of this study are the Office of Islamic Sharia shows that the Internal and External Communications implemented by the Islamic Sharia Service of Southeast Aceh Regency have been able to reduce the violations of Islamic Sharia, with 29 Civil Servants, from various disciplines and levels of rank. From the results of the study, it is recommended that the Islamic Sharia Service continue to convey to da'wah cadres or youth the application of Islamic Sharia. And the internal and external communications of the Islamic Sharia Service are mutually reinforcing, interconnected, and mutually influencing each other. In order to create conducive conditions, especially in the Southeast Aceh district.